Enhancing the Role of Christianity in Overcoming Economic Difficulties in Southeastern Nigeria Caused by Expensive Traditional Funeral Costs - Dimgba Esowe (International Journal of Sociology of Religion, 2025)
The belief in consciousness after death by African Traditionalists and its consequent customary burial ritual demands have created economic burdens for many of the people of South Eastern Nigeria. These rituals that are believed to aid the transition of the dead into the ancestral world of spirits require killing of animals such as fowls, goats, and cows as the case may be. Added to these are several steps of information chain that have to be followed before burials are conducted. The enormous funds that go into these processes in comparison to income levels of the people have left many a family in Igbo Land travailing economically. Thus it becomes expedient for the Christian religion founded by Christ Jesus for the alleviation of the sufferings of mankind to improve on its teachings on the state of the dead. Through the lifeworld phenomenological method, this work avails the Christian religion insights that should enhance its role in educating the people of South Eastern Nigeria on the truth about the state of the dead and how best to invest their income for a better life among the living.